2013
DOI: 10.15369/sujms.25.223
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Calcareous Concretions in the Capsules of Human Pineal Glands

Abstract: : We examined calcareous concretions in the capsule of 15 human pineal glands containing a large amount of the concretions in the matrix. The capsule concretions, brown to blackish-brown in color and / or translucent, were smaller than the matrix concretions, which were yellowish-white. The matrix concretions showed the typical mulberry-shaped overall appearance with scallop-shaped concentric laminations of non-brous structures, but the capsule concretions, which also contained Ca and P, showed a globular or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Magnesium whitlockite (MgWH; Ca 18 Mg 2 (HPO 4 ) 2 (PO 4 ) 12 ) has been reported to deposit in the human body, for example, dental calculi of human tooth enamel, [1][2][3] human articular cartilage, 4 and hyper-mineralized osteocyte and lacunae in human alveolar bone. 5 In a recent study, Hang et al 6 demonstrated that MgWH is an osteoconductive material with resorbability intermediate between the resorbabilities of hydroxyapatite and β-tricalcium phosphate (β-TCP).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium whitlockite (MgWH; Ca 18 Mg 2 (HPO 4 ) 2 (PO 4 ) 12 ) has been reported to deposit in the human body, for example, dental calculi of human tooth enamel, [1][2][3] human articular cartilage, 4 and hyper-mineralized osteocyte and lacunae in human alveolar bone. 5 In a recent study, Hang et al 6 demonstrated that MgWH is an osteoconductive material with resorbability intermediate between the resorbabilities of hydroxyapatite and β-tricalcium phosphate (β-TCP).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a low negative trend between aging and the mineralized volumes of the deposits by microradiography. We also recently observed fibrous calcareous concretions associated with characteristic minute spherical deposits MSD including a larger relative amount of Na as well as Ca and P in the capsule of a human pineal body and a large number of nonfibrous calcareous concretions in the matrix 2 .…”
Section: Introductionmentioning
confidence: 70%